Co-evolution of Friendships and Antipathies: A Longitudinal Study of Preschool Peer Groups - Daniel, João R.; Santos, António J.; Antunes, Marta; Fernandes, Marília; Vaughn, Brian E. (Frontiers in Psychology, 2016)
We used stochastic actor-based models to test whether the developmental dynamics of friendships and antipathies in preschool peer groups (followed throughout three school years) were co-dependent. We combined choices from three sociometric tasks of 142 children to identify friendship and antipathy ties and used SIENA to model network dynamics. Our results show that different social processes drive the development of friendship and antipathy ties, and that they do not develop in association (i.e., friendship ties are not dependent on existing antipathies, and vice-versa). These results differ from those of older children (age range = 10–14) suggesting that the interplay of friendship and antipathy only plays a significant role in the peer group context in older children. We propose these differences to be likely related with preschool age children's inaccurate perceptions of their classmates' relationships, particularly of their antipathies, and/or with the absence of shared norms to deal with antipathetic relationships.